RESTORASI KENMU (1333-1336): EKSPERIMEN POLITIK KAISAR GO-DAIGO - Eka Marthanty Indah Lestari (Universitas Diponegoro, 2016)
This article describes the Kenmu Restoration and several important historical events that happened around that time. Kenmu Restoration or Kenmu no Shinmei is a historic period in Japan from 1333 to 1336. This restoration marks 3 year period between the fall of Kamakura Bakufu and the rise of Ashikaga Bakufu. The essence of Kenmu Restoration as the political experiment by Emperor Go-Daigo is to give the same opportunity for nobleman and army to run the government. However, this idea cannot be realized as there was conflict between nobleman and army. The nobleman assumed that the political power must be returned to the Emperor and nobleman has right to control the government. On the contrary, army who fought to return the authority of Emperor also demanded the compensation, position in the government. Therefore, Kenmu Restoration at last failed. Ashikaga Takauji, the follower of Emperor Go-Daigo, was angry when the Emperor refused to appoint him as Shogun. As the result, Ashikaga Takauji sent his troops to destroy Emperor Go-Daigo. It indicates the rise of Ashikaga Bakufu.